Gambaran Penggunaan Media Sosial dan Pemanfaatan Informasi Kesehatan - Efendi, Mochammad Nauval Asraf; Irasanti, Siska Nia; Dananjaya, Rio (Jurnal Riset Kedokteran, 2025)
Abstract. The advancement of information technology has facilitated public access, including that of medical students, to health information through social media. This study aims to describe the types of social media used, the duration of usage, and the characteristics of health information utilization, which include the types of information, forms of information, and the most trusted sources of information among students. This research employed a descriptive quantitative design with a cross-sectional approach and utilized a questionnaire as the data collection instrument. The results showed that the most commonly used social media platform was WhatsApp (75.67%), with a usage duration of more than 4 hours per day (55.08%). The most frequently accessed health information included education, health learning materials, and disease prevention (34.46%). The most easily understood form of information was video (93.24%), and the most trusted source of information was from healthcare professional accounts (42.57%). The conclusion of this study indicates that social media plays a significant role in the utilization of health information among students; however, digital literacy is necessary to enable them to filter accurate and reliable information. Abstrak. Kemajuan teknologi informasi telah memudahkan masyarakat, termasuk mahasiswa kedokteran, dalam mengakses informasi kesehatan melalui media sosial. Penelitian ini bertujuan untuk mengetahui gambaran jenis media sosial, durasi penggunaan media sosial, serta karakteristik pemanfaatan informasi kesehatan yang mencakup jenis informasi, bentuk informasi, dan sumber informasi yang paling dipercaya oleh mahasiswa. Penelitian ini menggunakan desain deskriptif kuantitatif dengan pendekatan cross-sectional dan instrumen kuesioner. Hasil penelitian menunjukkan bahwa media sosial yang paling banyak digunakan adalah WhatsApp (75,67%) dengan durasi penggunaan lebih dari 4 jam per hari (55,08%). Jenis informasi kesehatan yang paling banyak diakses adalah edukasi, pembelajaran kesehatan, dan pencegahan penyakit (34,46%). Bentuk informasi kesehatan yang paling mudah dipahami adalah video (93,24%), dan sumber informasi yang paling dipercaya berasal dari akun tenaga kesehatan (42,57%). Simpulan penelitian ini menunjukkan bahwa media sosial berperan penting dalam pemanfaatan informasi kesehatan di kalangan mahasiswa, namun dibutuhkan literasi digital agar mereka mampu menyaring informasi yang akurat dan terpercaya.